Peptides of Laennec® preparation that contribute to the elimination of endotheliopathy - I. Yu. Torshin; О. А. Gromova; V. G. Zgoda; А. G. Chuchalin; V. А. Maksimov; О. V. Tikhonova (IRBIS LLC, 2022)
Objective: identification of peptides in the composition of Laennec®, which can inhibit the development of endotheliopathy (endothelial dysfunction).Material and methods. Hybrid mass spectrometry followed by data analysis based on topological recognition theory was performed. The analysis of the peptide composition of Laennec® included four stages: purification of the drug, chromatographic separation of peptides, determination of the multidimensional mass spectrum of the peptide fraction, and de novo sequencing of the isolated peptides.Results. The preparation contains peptides-inhibitors of specific target proteins (PRKCZ, PKB, PKD1, MAPK14, IKKB, PDPK1) involved in the activation of the pro-inflammatory transcription factor NF-κB. Inhibition of CDK5 and SHC1 kinases helps to reduce endothelial cell apoptosis. The peptides of the drug also block enzymes involved in the synthesis and maturation of the tumor necrosis factor alpha (MAPKAPK2/3, ADAM17).Conclusion. In the composition of Laennec®, peptides have been found that contribute to a complex pathogenetic action against endotheliopathy. Endothelial regeneration is especially important in the rehabilitation of patients who have recovered from COVID-19.